Three days at Camp David : how a secret meeting in 1971 transformed the global economy - Garten, Jeffrey E., 1946- (Harper, an imprint of HarperCollins Publishers, 2021)
"The former dean of the Yale School of Management and Undersecretary of Commerce in the Clinton administration chronicles the 1971 August meeting at Camp David, where President Nixon unilaterally ended the last vestiges of the gold standard--breaking the link between gold and the dollar--transforming the entire global monetary system"--